Toolkit for trainers : a compendium of techniques for trainers and group workers - Pickles, Tim (Fisher Books TucsonUS, 1996)
Contains 59 techniques/activities/exercises for use in training and developing groups such as: training groups, task-based groups, problem-solving groups, and mutual-support groups. Provides models for understanding groups. Presents techniques/tools for learning, evaluation, co-working, and coping with problems. Describes each technique using, some or all of the following headings: purpose; method; examples of the technique; worksheet or handout; possible variations; and, suitability.